The theology of the Gospel of John - Smith, D. (New Testament theology, 1994)
D. Moody Smith treats the theology of the Gospel of John in its narrative form and historical context, both ancient Jewish and early Christian. His work draws upon the most recent scholarly investigations of the Gospel's historical purpose and setting. The major theological themes of the Gospel, especially its christology, are treated in relation to the context of the work, since Johannine theology is not simply a by-product of controversies that produced the Gospel, but is rather related to them in significant ways. As Professor Smith shows, John marks an important watershed between Christianity and Judaism. His study will thus serve equally well as an introduction to the question of the origin of John and as an introduction to its theology. It also consistently pays attention to the relationship of the Gospel to other major New Testament witnesses as well as to its important influence upon the development of later Christian doctrine.